(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
A brief sketch of marketing and definition of social marketing, and the difference between the two are presented. Social marketing is the application and technique of marketing to gain social benefit. And consist of planning, implementing and controlling components of the program. Its aim to increase the adoption of practice or a certain social idea by the target subject audience. l1ndonesia has enacted social marketing, such as Blue Circle Family Planning. In health sector, Oralit; Generic drug; National Immunization Week; Iodized salt; Long-lasting impregnated bed net (anti-malaria) dan Mother's milk. Social1 Marketing for Nutrition basic theory and model is in the realm/ domain of health promotion. And its category, type of health promotion activities, and ethics outlined. We are using the PRECEDE and ELM models as. a basic social marketing campaign.gn to change the consumer to adopt the new behaviour to accept the new social product. The 4 -P components of social marketing also outlined, name.ly, product, price, promotion, and point of distribution. Its aim targeted to the consumer, subsequently presented the process and the social marketing campaign, whenever possible, we presented the factual experience. examples. The key word, first, the important condition do not launch a social marketing campaign, unless the product distribution available in the point of sal.es/ distribution. Second, program planner have to know the target consumer, inside-out And remember that behaviour, time sequence, according to their location target subject always change. Third, use the lesson l.eamt from social marketing campaign of impregnated bed net for anti malaria. And the planning, implementation, monitoring and evaluation and pi.ttaM experience of the lodged Salt campaign, see attachment. Fourth, health social marketing nutrition should be complimentary to the existing nutrition program. Fifth, roughly this paper outlined description content nutrition specialist 'Nith social marketing specialist; communication; behaviour, ethnographers dan other related specialist. Specifically owned the developing, and process oi creating a message., 'Nith collaboration, partnership 'Nith stakeholders network, See attachment the case of producing, marketing of commercial album audio cassette pop song that contain" Jangan Dulu - Wait a White, My Love," for postponing marriage, of young people. For the health social marketing-nutrition campaign by using the multi media mix, it. should be complemented with interpersonal health education by health providers, as a back up for overcoming the side effects and to maintain and to secure for consumer to accept the health program. In conclusion, social marlceting1 is just one effort to promote1 health. In general, social marketing implemented with health advocacy to speed up the largest objective of social marketing program. The health social marketing in nutrition is a concept development, of knowledge lhat program pl1anner, nutritionist can used for promoting good nubition for benefit of the needy community.